The Patient-Physiotherapist Tango: a Personalized Approach to ACL Recovery -- a Qualitative Interview Study - Ramana Piussi; Ella Brandt; Alicia Johansson; Thorkell Snaebjörnsson; Roland Thomeé; Kristian Samuelsson; Eric Hamrin Senorski (International Journal of Sports Physical Therapy)
# Background